Dança improvisação e permanência estudantil de autista no ensino superior: relato de experiência - Costa, Samea (2023)
In order to broaden the discussion about the permanence of autistic students in higher education, as well as to contribute to the disruption of capacitacy about the competence of the autistic subject in the university, this study aims to describe the contributions of regular classes of improvisation in dance in the student permanence of an autistic in higher education. In this sense, it is a descriptive study, type experience report, carried out through the participation of one of the autistic and university authors in the extension project dance and autism, Federal University of Sergipe, Brazil linked to the dance group Técnica Aplicada Lavínia Teixeira (TALT), which works since 2007 from the intersection dance and people with disabilities. The experience of dance improvisation in the university environment, with frequency of twice a week and duration of one hour per class, for a period of eight weeks, was explored by autistic students. Exchanges of experiences at the end of classes were also held. The article offers a comprehensive analysis of this enriching experience and its implications.